2016
DOI: 10.20527/jbk.v12i2.1862
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Status Gizi Dengan Lama Hari Rawat Inap Pasien Anak Diare Akut

Abstract: Good nutritional status can reduce the risk of diarrhea, while children with less or poor nutritional status enables more frequent and more susceptible to diarrhea. The worse the nutrition of a children, the frequency of diarrhea increases. This situation may have a relationship with length of stay. Length of stay of childhood diarrhea is influenced by the child's physical condition (good nutritional status, less, or worse). The purpose of this study is analyzing the relationship between nutritional status and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
7
0
3
Order By: Relevance
“…However, a study conducted in RSUD Ulin Banjarmasin and Desi Primayani (2009) also showed no correlation between nutritional status and the length of hospitalization of patients. 13,14 Malnutrition caused structural changes such as mucosal villi atrophy, disruption of enzyme disaccharide activities, the disorder of monosaccharide absorption, abnormal intestinal motility, and changing the intestinal flora. Malnutrition involved several mechanisms including; suppression of immune factors, changing the structure of the intestinal mucosa, and micronutrient deficiencies of zinc and vitamin A.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study conducted in RSUD Ulin Banjarmasin and Desi Primayani (2009) also showed no correlation between nutritional status and the length of hospitalization of patients. 13,14 Malnutrition caused structural changes such as mucosal villi atrophy, disruption of enzyme disaccharide activities, the disorder of monosaccharide absorption, abnormal intestinal motility, and changing the intestinal flora. Malnutrition involved several mechanisms including; suppression of immune factors, changing the structure of the intestinal mucosa, and micronutrient deficiencies of zinc and vitamin A.…”
Section: Discussionmentioning
confidence: 99%
“…Terapi gizi yang tepat akan meningkatkan indikator klinis dan biokimia sehingga pasien mempunyai ketahanan tubuh yang baik dan risiko komplikasi yang rendah. 5,6 Penelitian yang sudah pernah dilaksanakan yaitu penelitian mengenai hubungan antara status gizi awal dengan status pulang dan lama rawat inap pasien dewasa yang dilakukan di 3 (tiga) Rumah…”
Section: Penerbit : Fakultas Kedokteran Universitas Muslim Indonesiaunclassified
“…The advantages of implementing TGM are reducing the Length of Stay (LOS), helping to accelerate healing, preventing further risk factors, improving quality of life, and saving costs. Objective: To analyze the outcome of malnutrition patients who received nutritional therapy in Ibnu Sina Hospital Makassar in 2015-2016 This study is an analytical study with a cross-sectional approach, using consecutive sampling techniques. The research sample is the medical record of malnutrition patients according to inclusion and exclusion criteria who were treated at Ibnu Sina Makassar Hospital in [2015][2016].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of changes in shape to be like bound piles, EPEC can form a microcolony which produces a localized adherence pattern. This damaged epithelial structure results in the decreased absorptive capacity of the intestinal mucosa and loss of tight junction integrity that leads to reduced epithelial resistance, increased membrane permeability, disruption of Na + K + pumps, and inhibition of water and electrolyte absorption which causes diarrhea [7]. This mechanism of inflammation caused by EPEC renders damage to the small intestine's histopathology [7].…”
Section: Introductionmentioning
confidence: 99%